Using Drop Jumps and Jump Squats to Assess Eccentric and Concentric Force-Velocity Characteristics - Gavin L. Moir; Brandon W. Snyder; Chris Connaboy; Hugh S. Lamont; Shala E. Davis (MDPI AG, 2018)
The purpose of this study was to investigate the eccentric and concentric force-velocity (Fv) characteristics recorded during drop jumps (DJ) from different heights and loaded jump squats (JS) and to determine the number of jumps required to accurately model the eccentric and concentric Fv relationships. Fourteen resistance-trained men (age: 21.9 ± 1.8 years) performed a countermovement jump (CMJ) and DJ from heights of 0.40, 0.60, and 0.80 m. JS with loads equivalent to 0%, 27%, 56%, and 85% 1-repetition maximum were performed in a separate session. Force platforms and a 3-D motion analysis system were used to record the average force ( <semantics> <mover accent="true"> F ¯ </mover> </semantics> ) and velocity ( <semantics> <mover accent="true"> v ¯ </mover> </semantics> ) during the absorption (CMJ, DJ40, DJ60, DJ80) and propulsion (JS0, JS27, JS56, JS85) phases of the jumps. Eccentric (absorption phase) and concentric (propulsion phase) Fv characteristics were then calculated and linear regression equations were determined when the number of jumps included was varied. <semantics> <mover accent="true"> F ¯ </mover> </semantics> during the absorption phase significantly increased from CMJ to DJ60 while <semantics> <mover accent="true"> v ¯ </mover> </semantics> increased significantly from CMJ to DJ80. The two-point method (CMJ, DJ80) resulted in a significantly lower y-intercept (mean difference [MD]: 0.7 N/kg) and a greater slope (MD: 0.7 Ns/m) for the eccentric Fv characteristics compared to the multiple-point method. <semantics> <mover accent="true"> F ¯ </mover> </semantics> increased significantly and <semantics> <mover accent="true"> v ¯ </mover> </semantics> decreased significantly with increasing external load in the JS conditions. The two-point method (JS0, JS85) resulted in a significantly greater y-intercept (MD: 1.1 N/kg) compared to the multiple-point method for the concentric Fv characteristics. Both DJ and loaded JS may provide means of assessing the eccentric and concentric Fv characteristics with only two jumps being required.